Practicing an ethic of discomfort as an ethic of care in higher education teaching - Zembylas, Michalinos (Critical Studies in Teaching and Learning, 2023)
In this article, I address the issue of how we can instil pedagogical practices in higher education   with   ethical   and   political   significance   so   that   the   hegemonic   rationalist epistemology of educational development is interrupted.  To do this, I take up two recent streams of response to this challenge; one focused on care and the other on discomfort. Illustrating the tensions and possibilities that the notion of the ‘ethic of care’ and ‘ethic of discomfort’ may have in discourses of educational development is the focus of this article. In particular, the following three questions structure my discussion: What are the contributions and limits of the ethic of care in exploring issues of educational development in our contemporary globalised world? How can the scope of care and caring teaching be extended through   an   ethic   of   discomfort?   Finally, what   are   the   implications   for   educational development   of   such   a   reconceptualization   of   care   on   the   basis   of  ‘pedagogies   of discomfort’? To approach these questions I first consider some theoretical conversations regarding caring teaching in (higher) education, pointing out the possibilities as well as some limitations. Then I discuss the reconceptualisation of caring teaching in higher education on the basis of an ethic of discomfort. Following this, I lay out some implications for educational development   and   teaching   in   higher   education   and   answer   the   question   of   how   a reconceptualised ethic of care through discomfort can contribute to reconsidering mainstream perceptions of and pedagogical practices in higher education.